If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 51 = 3(4v + 1) Reorder the terms: 51 = 3(1 + 4v) 51 = (1 * 3 + 4v * 3) 51 = (3 + 12v) Solving 51 = 3 + 12v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-12v' to each side of the equation. 51 + -12v = 3 + 12v + -12v Combine like terms: 12v + -12v = 0 51 + -12v = 3 + 0 51 + -12v = 3 Add '-51' to each side of the equation. 51 + -51 + -12v = 3 + -51 Combine like terms: 51 + -51 = 0 0 + -12v = 3 + -51 -12v = 3 + -51 Combine like terms: 3 + -51 = -48 -12v = -48 Divide each side by '-12'. v = 4 Simplifying v = 4
| 1/4y=6 | | X-2X^4=0 | | x^2+2x-3=7 | | 7d-1=90 | | (z-3)(2z+10)(z-1)= | | 4(3x-1.6)=9x-6.4 | | 26=5x^2+7x+2 | | 4.2x-51=2.6x+5 | | y-8.8=8 | | 24/x | | 7(x-9.4)=2.1 | | 2x+27=45 | | 26=(2x+1)(3x+2) | | x^2(2x+3)=17x-12 | | 3/4b=4/6 | | x^3-x^2+5x-2=0 | | (8r+1)(r+2)=0 | | y-23=4y-19 | | 10-2(3x-5)=12 | | 4y-19=y-23 | | 3a+2x= | | x+(x-42)=90 | | (y+20)+(4y-15)=180 | | 4y-19+y-23=2x+27 | | c(3c+2)-3(c^2+4c-17)=1x | | 8(2l+7)=216 | | -1.5/-.3 | | 7n^2+8n+1=0 | | .01/2 | | -2(5n+2)=2 | | k^3-6k^2-21k=0 | | 4(2x-1.7)=4x-6.8 |